2004
DOI: 10.1097/00126097-200412000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Telemonitoring of blood pressure self measurement in the OLMETEL study

Abstract: In a 'real-life' clinical practice setting, telemonitoring of BPSM was an effective technique that was partially affected by patient non-compliance. Olmesartan medoxomil provided effective and reliable BP-lowering, which was maintained throughout the 24-hour period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 16 publications
0
18
0
3
Order By: Relevance
“…162 Several studies have demonstrated that effective control of hypertension can be achieved when patients using HBPM can communicate with their providers (either trained nurse clinicians or physicians) to adjust medication as needed to achieve goals for treatment. 125,[163][164][165] The significance of apparent control of hypertension with the use of HBPM with regard to prevention of cardiovascular morbidity and mortality is not established. In the aforementioned study, which compared HBPM with office management for hypertension and used the same BP goal for both office and home assessment, 113 the cost of treatment (medication) was slightly lower for the HBPM group because less medication was required for control, but the target level of BP (a diastolic pressure of 80 to 89 mm Hg) was higher than generally recommended.…”
Section: Costs and Savings Related To Implementation And Use Of Hbpmmentioning
confidence: 99%
“…162 Several studies have demonstrated that effective control of hypertension can be achieved when patients using HBPM can communicate with their providers (either trained nurse clinicians or physicians) to adjust medication as needed to achieve goals for treatment. 125,[163][164][165] The significance of apparent control of hypertension with the use of HBPM with regard to prevention of cardiovascular morbidity and mortality is not established. In the aforementioned study, which compared HBPM with office management for hypertension and used the same BP goal for both office and home assessment, 113 the cost of treatment (medication) was slightly lower for the HBPM group because less medication was required for control, but the target level of BP (a diastolic pressure of 80 to 89 mm Hg) was higher than generally recommended.…”
Section: Costs and Savings Related To Implementation And Use Of Hbpmmentioning
confidence: 99%
“…Además, varios estudios en pacientes hipertensos y cardiópatas han demostrado un alto nivel de cumplimiento de los programas de telemonitorización con una reducción de las cifras de presión arterial sistólica y diastólica (150)(151)(152)(153) .…”
Section: Resultados De Las Redes Inalámbricas Aplicadas a La Medicinaunclassified
“…A small amount of technical solutions have been tested in a number of application studies ). The virtually Clinic of Hypertension was tested successfully in several pharmacological studies (Ewald S et al, 2006;Mengden T et al, 2004;Möckel V et al, 2009). In all these studies telemetric blood pressure measurement was proved as practicable and was well accepted by the majority of the treated patients.…”
Section: Application Of Telemetric Blood Pressure Measurement In the mentioning
confidence: 99%